Information systems : intelligent information processing systems, natural language processing, affective computing and artificial intelligence, and an attempt to build a conversational nursing robot /: intelligent information processing systems, natural language processing, affective computing and artificial intelligence, and an attempt to build a conversational nursing robot. (2021) - Unknown
No abstract available